2012
DOI: 10.1111/j.1469-8137.2012.04106.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to environmental desiccation in moss sperm

Abstract: Summary• Sexual reproduction in mosses requires that sperm be released freely into the environment before finding and fertilizing a receptive female. After release from the male plant, moss sperm may experience a range of abiotic stresses; however, few data are available examining stress tolerance of moss sperm and whether there is genetic variation for stress tolerance in this important life stage.• Here, we investigated the effects of environmental desiccation and recovery on the sperm cells of three moss sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 127 publications
(147 reference statements)
1
22
0
Order By: Relevance
“…On the one hand, although sperm cells might tolerate desiccation for extended periods (Shortlidge, Rosenstiel & Eppley 2012), sexual reproduction depends on sperms swimming to eggs via a continuous film of water. As a consequence, fertilization ranges, which are of one to a few tens of decimetres (Bisang, Ehrl en & Heden€ as 2004;Rydgren, Cronberg & Økland 2006), are extremely short as compared to angiosperm's pollen ranges.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, although sperm cells might tolerate desiccation for extended periods (Shortlidge, Rosenstiel & Eppley 2012), sexual reproduction depends on sperms swimming to eggs via a continuous film of water. As a consequence, fertilization ranges, which are of one to a few tens of decimetres (Bisang, Ehrl en & Heden€ as 2004;Rydgren, Cronberg & Økland 2006), are extremely short as compared to angiosperm's pollen ranges.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies showed that dioicous mosses are more genetically diverse than would be expected with such dispersal limitation (Wyatt et al, 1989;Van der Velde et al, 2001;Wilson and Provan, 2003). Indeed several studies have since demonstrated greater sperm dispersal distances (for a review, see Glime, 2007), as well as stresstolerant sperm (Rosenstiel and Eppley, 2009;Shortlidge et al, 2012) and microarthropod-mediated sexual reproduction (Cronberg et al, 2006;Cronberg, 2012;Rosenstiel et al, 2012). Other factors can limit sexual reproduction in mosses, including: inadequate resources (Stark et al, 2000) growth trade-offs (Ehrlén et al, 2000) and investment in environmental stress defence (Convey and Smith, 1993;Stark et al, 2009;Eppley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Schofield (1971) discussed how low levels of free water along with the generally isolated patches of mostly dioicous (>60%) species (which may form single sex colonies) may limit sexual reproduction in the Arctic. Recent studies have shown, however, that sexual reproduction can occur in environments with only short-term availability of free water, as sperm cells and antheridia can withstand dehydration (Shortlidge et al 2012;Stark et al 2016). Monoicous acrocarpous taxa tend to reproduce sexually regularly (Schofield 1971;Longton 1988), but phenological data are lacking or incomplete for most taxa.…”
Section: Long-distance Dispersalmentioning
confidence: 99%